The Neuroprotective Effects of Experience on Cognitive Functions: Evidence from Animal Studies on the Neurobiological Bases of Brain Reserve. (1st February 2018) - Gelfo, Francesca; Mandolesi, Laura; Serra, Laura; Sorrentino, Giuseppe; Caltagirone, Carlo
Highlights: By shaping brain structure and function, stimulating experience is able to create a protective reserve. The brain cellular and molecular reserve mechanisms have been investigated using environmental enrichment paradigm. Animal studies show that environmental enrichment induces brain rearrangements at both cellular and molecular levels. Brain reserve permits a better ability to cope with the cognitive decline that is linked to normal and pathological ageing. Novel studies and systematic reviews that consider the different components of environmental enrichment are needed. Abstract: Brain plasticity is the ability of the nervous system to change structurally and functionally in response to experience. By shaping brain structure and function, experience leads to the creation of a protective reserve that accounts for differences among individuals in susceptibility to age-related brain modifications and pathology. This review is aimed to address the biological bases of the experience-dependent "brain reserve" by describing the results of animal studies that focused on the neuroanatomical and molecular effects of environmental enrichment. More specifically, the effects at the cellular level are considered in terms of changes in neurogenesis, gliogenesis, angiogenesis, and synaptogenesis. Moreover, the effects at the molecular level are described, highlighting gene- and protein-level changes in neurotransmitter and neurotrophin expression. The experimental evidence for the basic biological consequences of environmental enrichment is described for healthy animals. Subsequently, by discussing the findings for animal models that mimic age-related diseases, the involvement of such plastic changes in supporting an organism as it copes with normal and pathological age-related cognitive decline is considered. On the whole, studies of the structural and molecular effects of environmental enrichment strongly support the neuroprotective action of a particularly stimulating lifestyle on cognitive functions. Our current level of understanding of these effects and mechanisms is such that additional and novel studies, systematic reviews, and meta-analyses are necessary to investigate the specific effects of the different components of environmental enrichment in both healthy and pathological models. Only in this way can comprehensive recommendations for proper life habits be developed.